1970
DOI: 10.1136/bmj.2.5712.757
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pentazocine and Pethidine in Labour

Abstract: Dysuria in Women-Waters et al. IIRMM 757dysuria is commoner in women who have had children (Waters, 1969) whereas age-adjusted mean systolic and diastolic blood pressures decrease with the number of children (Miall and Oldham, 1958).Fifty-three (1-8°,') of the women seen during the initial screening survey dated their first attack of dysuria' to childhood. A oomparison of symptoms in these women ;with those who had dysuria only in adult life suggests that their symptoms are more severe and more frequent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…doses of 30 to 45 mg pentazocine during labour (Filler and Filler, 1966;Moore et al, 1970), and Apgar scores in infants born after the administration of pentazocine were similar to those obtained after the administration of pethidine (Duncan et al, 1969;Moore et al, 1970;Mowat et al, 1970). 1,2,3,4,S,6-hexahydro-S-hydroxy..{i-ll-dimethyl-3-(3-methylbut-2-eny1)-2,6-methano-3benzazocine 4.1 Synonyms Also known by the research code name Win20,228 and the trade names Fortalgesic, Fortral , Fortralin, Sosegon and Talwin.…”
Section: Placental Transfersupporting
confidence: 58%
See 4 more Smart Citations
“…doses of 30 to 45 mg pentazocine during labour (Filler and Filler, 1966;Moore et al, 1970), and Apgar scores in infants born after the administration of pentazocine were similar to those obtained after the administration of pethidine (Duncan et al, 1969;Moore et al, 1970;Mowat et al, 1970). 1,2,3,4,S,6-hexahydro-S-hydroxy..{i-ll-dimethyl-3-(3-methylbut-2-eny1)-2,6-methano-3benzazocine 4.1 Synonyms Also known by the research code name Win20,228 and the trade names Fortalgesic, Fortral , Fortralin, Sosegon and Talwin.…”
Section: Placental Transfersupporting
confidence: 58%
“…Differences between the two pethidine groups, and between pethidine 100 mg and pentazocine 40 mg were not statistically significant. These workers, like Levy (1971) observed a tendency for the second dose of pentazocine to provide relief of pain in a smaller proportion of patients than the first dose, but this tendency has not been confirmed by others (Duncan et al, 1969;Mowat and Garrey, 1970). In a study involving 98 predominantly multiparous patients, O'Dwyer (1971) reported pain relief at 1 hour in 44 % of those given pentazocine 30 mg and in 54 % given a combination of pethidine 100 mg and levallorphan 1.25 mg. No significant difference in the degree of pain relief afforded by either drug was demonstrated (p > 0.05).…”
Section: Obstetricsmentioning
confidence: 95%
See 3 more Smart Citations